Participatory scenario building for climate resilience: a guide tested in Ghana - Osei-Amponsah, Charity; Quarmine, William (International Water Management Institute, 2025)
The guide, Participatory Scenario Building for Climate Resilience, offers a practical framework for inclusive climate resilience planning, tested in Ghana. It emphasizes the need for participatory approaches to address climate risks and vulnerabilities, especially among marginalized groups. Using the Three Horizons Framework, the guide helps communities analyze current climate challenges (H1), envision resilient futures (H3), and identify transformative pathways (H2). It outlines six phases: preparation, vulnerability assessment, envisioning futures, identifying pathways, action planning, and monitoring. Tools such as the Vulnerability Assessment Matrix and Participatory Capacity and Vulnerability Analysis (PCVA) support structured analysis. The guide also provides facilitation techniques to ensure inclusive, equitable participation and strong community ownership. It is tailored for community leaders, planners, nongovernmental organizations, and local officials engaged in climate adaptation efforts.